Impact of Ethnicity on Donor Search Results for Children Requiring Stem Cell Transplantation. Issue 3 (April 2015) - DiLabio, Julia; Doyle, John; Alexander, Sarah; Gupta, Sumit; Punnett, Angela
<x xml:space="preserve">Abstract</x> Hematopoietic stem cell transplantation (HSCT) can be curative for children with various malignant and nonmalignant conditions. Access to suitable unrelated living donors (ULDs) or unrelated cord blood (UCB) may be limited for certain ethnic backgrounds. We therefore determined the impact of ethnicity upon donor availability in a pediatric cohort referred for allogeneic HSCT to a single Canadian transplant center. Among 252 eligible patients, 58 (23.0%) had suitable family donors. Of 161 patients with combined ULD and UCB searches, 78 (48.4%) had a suitable ULD, whereas 143 (88.8%) had suitable UCB. The probability of finding a suitable ULD differed significantly by ethnicity (P=0.007). Non-white patients were significantly less likely to have suitable ULDs (odds ratio [OR] 0.35; 95% confidence interval [CI], 0.17-0.69; P=0.003) compared with white patients but were equally likely to have suitable UCB (OR 1.02; 95% CI, 0.36-2.89; P=0.97). Although ethnic disparities exist in pediatric patients' access to ULD for HSCT, they are narrowed by the availability of international UCB registries. These findings, however, also highlight the importance of continued recruitment of individuals of non-white ethnicities to donor registries.